Strategi Industri Pada Ekonomi Makro Di Kota Surabaya - David Setiawan; Edelweis Bunga Gunung; Muhammad Yasin (International Forum of Researchers and Lecturers, 2023)
This journal investigates industrial strategies that are relevant in the context of macroeconomics in the city of Surabaya. Surabaya, as one of the largest cities in Indonesia, has an important role in industrial development and national economic growth. The purpose of this study is to analyze various industrial strategies that can be used to strengthen the city's macro-economy. The research method used in this study involves the analysis of secondary data obtained from reliable sources, including government reports, industry case studies, and related literature. Based on the data analysis, several industrial strategies that have proven effective in influencing the macro-economy in the city of Surabaya are identified and evaluated..